Assessing Pain in Infancy: The Caregiver Context - R Pillai Riddell; Nicole Racine (Pain Research and Management)
BACKGROUND: Pain is largely accepted as being influenced by social context. Unlike most other developmental stages throughout the lifespan, infancy is marked by complete dependence on the caregiver. The present paper discusses the primary importance of understanding the caregiver context when assessing infant pain expression.